Homologated amino acids with three vicinal fluorines positioned along the backbone: development of a stereoselective synthesis - Cheerlavancha, Raju; Ahmed, Ahmed; Leung, Yun Cheuk; Lawer, Aggie; Liu, Qing-Quan; Cagnes, Marina; Jang, Hee-Chan; Hu, Xiang-Guo; Hunter, Luke (Beilstein Journal of Organic Chemistry, 2017)
Backbone-extended amino acids have a variety of potential applications in peptide and protein science, particularly if the geometry of the amino acid is controllable. Here we describe the synthesis of δ-amino acids that contain three vicinal C–F bonds positioned along the backbone. The ultimately successful synthetic approach emerged through the investigation of several methods based on both electrophilic and nucleophilic fluorination chemistry. We show that different diastereoisomers of this fluorinated δ-amino acid adopt distinct conformations in solution, suggesting that these molecules might have value as shape-controlled building blocks for future applications in peptide science.
Keywords: amino acids; conformation; deoxyfluorination; fluorine; stereochemistry